Temperature sensitivity based on channel length of FinFET transistor - Atalla, Yousif; Hashim, Yasir; Abdul Nasir, Abd Ghafar (JACS, 2018)
This paper presents the temperature sensitivity of the gate length-based fin field effect transistor (FinFET) and the possibility of using such a transistor as a nano-temperature sensor. The multi-gate field effect transistor (MuGFET) simulation tool is used to investigate the temperature characteristics of FinFET. Current–voltage characteristics with different temperatures and gate lengths (Lg = 25, 45, 65, 85 and 105 nm) are initially simulated, then the metal oxide semiconductor diode mode connection to measure FinFET temperature sensitivity is considered. The best temperature sensitivity of the FinFET is observed on the basis of the largest ∆I at the working voltage VDD range of 0–5 V. Furthermore, temperature sensitivity of the FinFET increased linearly with channel length at the range of 25–105 nm.